2020
DOI: 10.1108/pap-04-2020-0023
|View full text |Cite
|
Sign up to set email alerts
|

Public-Private Partnership for achieving sustainable development goals: a case study of Khulna, Bangladesh

Abstract: PurposePublic-Private Partnership (PPP) is a common practice in both the public and private sectors. PPP has been an important instrument to achieve Sustainable Development Goals (SDGs) at the national level. However, the role of PPP at the subnational level is often scarcely studied. Using Khulna city of Bangladesh as a case, this paper aims to assess the role of PPP projects in the attainment of SDGs.Design/methodology/approachThe research was conducted in the Central Business District (CBD) of Khulna, on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 16 publications
0
16
0
1
Order By: Relevance
“…Despite a large number of public-private partnership (PPP) projects under the central government of Bangladesh, in areas of energy, transport, port, water supply, etc., very few PPP projects are under the local government, and most of them are confined to solid waste [ 11 ]. A study by Water & Sanitation for the Urban Poor (WSUP) revealed that PPPs offer a strong platform for developing approaches to FSM in Bangladesh [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite a large number of public-private partnership (PPP) projects under the central government of Bangladesh, in areas of energy, transport, port, water supply, etc., very few PPP projects are under the local government, and most of them are confined to solid waste [ 11 ]. A study by Water & Sanitation for the Urban Poor (WSUP) revealed that PPPs offer a strong platform for developing approaches to FSM in Bangladesh [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bangladesh is a developing country and has been moving forward to become a developed country by 2041. The government has spent billions of US$ to meet urban infrastructure requirements (Haque et al , 2020). Urbanization is mainly due to push–pull factors in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…Khulna is one of the four major cities in Bangladesh that has more than one million population. Locating on the Bank of Bhairab-Rupsha River, Khulna City (officially known as Khulna City Corporation- KCC) has been developed as the main center of trade, commerce, industry, administration, health and education in the southwest region for half a century ( Haque et al., 2020 ). This city offers all kinds of urban amenities and services and has a well-developed transportation network, therefore, the city experiences a huge influx of people from nearby cities and regions ( Haque et al., 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Due to the lack of such market-based policy instruments (such as payment for ecosystem services- PES), the pond owners find it profitable to fill the pond for real-estate business. Therefore, it is urgent to develop a framework to conserve the remaining ponds and restore the degraded ones wherever possible to maintain a healthy urban environment in Khulna city ( Haquet et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%